1999
DOI: 10.1103/physrevb.60.7352
|View full text |Cite
|
Sign up to set email alerts
|

Micromagnetism and magnetization reversal of micron-scale (110) Fe thin-film magnetic elements

Abstract: Magnetic force microscope ͑MFM͒ imaging in conjunction with longitudinal Kerr hysteresis loop measurements have been used to investigate the micromagnetic behavior of micron scale epitaxial ͑110͒ bcc Fe thin-film elements ͑50-nm thick͒ with rectangular, triangular, and needle-shaped ends and competing magnetic anisotropies. Thin-film elements of 2-m width and 6-m length and greater have been fabricated with their long axis oriented either parallel or perpendicular to the ͓001͔ in-plane magnetocrystalline easy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…Therefore, detailed micromagnetic studies are of particular importance for tailoring the magnetic properties of such MRAM cells. This includes experiments on the magnetic switching 7,8 as well as micromagnetic simulations. 9,10 In this context a precise knowledge of magnetic anisotropy energies of the magnetic layers is of outstanding interest.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, detailed micromagnetic studies are of particular importance for tailoring the magnetic properties of such MRAM cells. This includes experiments on the magnetic switching 7,8 as well as micromagnetic simulations. 9,10 In this context a precise knowledge of magnetic anisotropy energies of the magnetic layers is of outstanding interest.…”
Section: Introductionmentioning
confidence: 99%
“…For epitaxial bcc Fe(1 1 0) thin ®lms grown on Al 2 O 3 (1 1 À2 0) substrates using a Mo buer it was already shown that the ®lm demagnetization factors con®ne the magnetization to the (1 1 0) plane [17]. In addition to the cubic magnetocrystaline anisotropy the Fe(1 1 0) plane has a strong inplane strain induced uniaxial anisotropy component along the [0 0 1] direction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the cubic magnetocrystaline anisotropy the Fe(1 1 0) plane has a strong inplane strain induced uniaxial anisotropy component along the [0 0 1] direction. Along the [0 0 1] direction the cubic and uniaxial anisotropy constants have been determined to K l 6:3 Â 10 5 erg/ cm 3 and K u 3:0 Â 10 5 erg/cm 3 , respectively [17]. The ®lms were grown by molecular beam epitaxy (MBE) which allows the controlled thin ®lm growth with sub-monolayer precision and high material purity.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows an MFM image of microstructured Fe( 11 0) ellipsoid-shaped elements with lateral dimensions of 1.5 flm 500 nm. Starting with a 25 nm thick iron film with (110) orientation these elements have been fabricated by using electron beam lithography and argon ion etching [6]. After applying a magnetic field of 1 Tesla perpendicular to the long axis of the elements -i.e.…”
Section: Snommentioning
confidence: 99%